PSYCHOSOMATIC ASPECTS OF THE COMBINED PATHOLOGY OF PERIODONTAL TISSUE AND ORAL MUCOSA - T.A. Petrushanko; N.N. Ilenko (Ukrainian Medical Stomatological Academy, 2018)
In the structure of modern diseases, there are 50-75% of psychosomatic diseases. To understand the role of the emotional factor in the onset and progression of somatic disorders, as well as the opposite process - the emergence of psychological and emotional disorders as a response to an acute or chronic disease of internal organs - acquires a particular importance and relevance at the present stage of the causality of the disease. Individual features of the response of the human body to social, biological factors have common mechanisms of combined damage to the mucous membrane of the oral cavity and periodontal tissue. The severity of the damage to these organs and tissues is also determined by the psychological characteristics of individuals. These points are important not only for understanding the causality of the combined pathology of the periodontal and oral mucosa, but also for choosing the optimal tactics for treating such dental patients. The aim of the work was to analyze the role of psychosomatic correlations in the occurrence and development of the combined pathology of the periodontal and oral mucosa, determining the tactics of their treatment. 32 patients were involved in the examination with pathological changes of periodontal and oral mucosa. The essential role of the emotional component in the genesis of diseases was confirmed. Taking into account the psychosomatic nature of the pathology in the experimental group of patients, recommendations were given on diet therapy, psychotherapy, autogenic training. General medical treatment for internists and dentists was maximally individualized, taking into account the psychological characteristics of the response to the disease, differentiated according to the nature of the existing diseases, severity, pathology. After 6 months of follow-up, a stable, reliable positive clinical result was obtained in all patients in the experimental group and in 64% in the control group. Accounting for the state of psychosomatic relationships in the mechanisms of origin, development, treatment of diseases is extremely important. This approach in the supervision of dental patients who have combined changes in periodontal tissues, the oral mucosa allows achieving positive results of treatment, both in relation to the condition of the oral cavity, and for the body as a whole.